Evolving Marriage Customs in the Brahmin and Chhetri Communities: A Case Study of Birendranagar Surkhet - Dakal, Bed Prakash (Journal of Contemporary Review, 2024)
This study examines changing marriage patterns within the Brahmin and Chhetri communities, focusing on shifts in attitudes toward rituals, gender roles, and social norms. It employed a mixed-methods approach and was limited to the Surkhet district due to financial and time constraints. Samabesi Tole has 129 households and a total population of 640, including 322 females and 318 males. Among these, 92 families belong to the Brahmin and Chhetri communities, with a combined population of 466. Data from both married and unmarried respondents show increased acceptance of remarriage, divorce, and inter-caste unions, along with a growing emphasis on individual choice and gender equality. Traditional ceremonies are increasingly being modified or shortened, blending Nepali and Indian customs influenced by modern trends. While some resist these changes to preserve cultural heritage, many view them as steps toward social progress. Expert opinions differ on whether these shifts divide or unite society, but overall, marriage seems to be a flexible institution shaped by education, modernization, and evolving social values. This study reflects an evolution of marriage customs among marginalized or indigenous groups in Nepal.